Comparison of IGRA tests and TST in the diagnosis of latent tuberculosis infection and predicting tuberculosis in risk groups in Krakow, Poland. (September 2014) - Kruczak, Katarzyna; Duplaga, Mariusz; Sanak, Marek; Cmiel, Adam; Mastalerz, Lucyna; Sladek, Krzysztof; Nizankowska-Mogilnicka, Ewa
Abstract Background: The objective of this study was to assess the prevalence of latent tuberculosis infection (LTBI) in risk groups in Krakow, using the QuantiFERON-TB Gold In-Tube (QFT-GIT) test and the tuberculin skin test (TST); we also sought to assess the rate of progression to active disease over 4–5 y of follow-up. Methods: QFT-GIT tests were performed on 785 subjects and the TST on 701 subjects from the risk groups of homeless persons, close contacts, periodic contacts, and residents of long-term care facilities (LTCFs), and subjects from a low risk group. Results: In homeless persons, close contacts, periodic contacts, LTCF residents, and low risk persons, a positive QFT-GIT was found in 36.7%, 27.2%, 27.0%, 21.1%, and 23.7% of subjects, respectively, while a positive TST was found in 55.8%, 47.4%, 47.6%, 43.2%, and 47.9%, respectively. Of 63 homeless subjects, 5 developed active TB over 248 person-y of follow-up (incidence rate (IR) 20 per 1000 person-y, 95% confidence interval (CI) 8.4–48.5); of 148 close contacts, 5 developed active TB over 740 person-y of follow-up (IR 7, 95% CI 2.8–16.2); of 145 periodic contacts, 2 developed active TB over 580 person-y of follow-up (IR 4, 95% CI 0.9–13.8). The IR per 1000 person-y (95% CI) among subjects with a positive QFT-GIT was 30 (9.0–86.1) for homeless subjects, 18 (5.7–54.7) for close contacts, and 13 (3.2–51.3) for periodic contacts. In Poland there is no policy for the provision of LTBI treatment to people with a positive QFT or TST; therefore, the estimated rates of disease progression were analysed amongst untreated subjects. Conclusions: The prevalence of positive QFT-GIT and TST was high in the study risk groups. The best predictor of active TB in the homeless and close contacts groups was a positive QFT-GIT together with a positive TST.